Disruption of Circadian Rhythms: A Crucial Factor in the Etiology of Infertility - Sciarra, Francesca (Int J Mol Sci, 2020)
Infertility represents a growing health problem in industrialized countries. Thus, a greater understanding of the molecular networks involved in this disease could be critical for the development of new therapies. A recent finding revealed that circadian rhythmicity disruption is one of the main causes of poor reproductive outcome. The circadian clock system beats circadian rhythms and modulates several physiological functions such as the sleep-wake cycle, body temperature, heart rate, and hormones secretion, all of which enable the body to function in response to a 24 h cycle. This intricated machinery is driven by specific genes, called “clock genes” that fine-tune body homeostasis. Stress of modern lifestyle can determine changes in hormone secretion, favoring the onset of infertility-related conditions that might reflect disfunctions within the hypothalamic–pituitary–gonadal axis. Consequently, the loss of rhythmicity in the suprachiasmatic nuclei might affect pulsatile sexual hormones release. Herein, we provide an overview of the recent findings, in both animal models and humans, about how fertility is influenced by circadian rhythm. In addition, we explore the complex interaction among hormones, fertility and the circadian clock. A deeper analysis of these interactions might lead to novel insights that could ameliorate the therapeutic management of infertility and related disorders.